Maternal mortality and its causes in a tertiary care hospital - Doke, Goter; Kamda, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal mortality is defined as the death of a woman while being pregnant or within 42 completed days of termination of pregnancy. The aim of this study was to study the maternal mortality and analyze the complications leading to maternal deaths. Methods: A retrospective study of hospital records and death summaries of all maternal deaths over the period of two year from April 2017 to March 2019 was conducted in the Department of Obstetrics and Gynecology, Tomo Riba Institute of Health and Medical Science, a tertiary level healthcare referral center in Naharlagun, Arunachal Pradesh, India. Results: There was a total of 6 maternal deaths out of 6311 live births giving maternal mortality ratio (MMR) of 95.07 per 1,00,000 live births. The majority of deaths were reported in the age groups 30-40 years (66.66%). More deaths were reported in multiparous women (83.33%) as compared to primiparous women (16.66%). Most of them were unbooked cases (66.66%). Haemorrhage (33.33) and pregnancy induced hypertension (33.33%) were the major direct cause of maternal deaths. Conclusions: Haemorrhage and pregnancy induced hypertension were found to be major cause of maternal deaths. In our study, there was no maternal death from anemia and other medical disorder.